2022
DOI: 10.12938/bmfh.2021-058
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of probiotics against tannin-induced immunosuppression in broiler chickens

Abstract: Tannins (TAs) are an anti-nutritional substance commonly used as a natural feed additive for livestock. However, our previous study described the dose-dependent adverse effects of TA on immune responses and growth in chickens. In this study, we evaluated the protective effects of a probiotic preparation (BT) consisting of three different bacteria ( Bacillus mesenteric, Clostridium butyricum, and Streptococcus faecalis ) against TA-induced immunosuppression in chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…The limitation of this study was a lack of evaluation of food consumption and the food conversion ratio in BT-fed piglets. However, in our previous study, growth promotion of probiotics to BT-fed chicks has been reported [ 14 ]. The body weight in BT-fed chicks was significantly increased in the study, but daily body weight gain and food intake did not significantly change between control and BT-fed chick groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The limitation of this study was a lack of evaluation of food consumption and the food conversion ratio in BT-fed piglets. However, in our previous study, growth promotion of probiotics to BT-fed chicks has been reported [ 14 ]. The body weight in BT-fed chicks was significantly increased in the study, but daily body weight gain and food intake did not significantly change between control and BT-fed chick groups.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, probiotic consumption in humans was associated with increased stimulation and activation of multiple immune cell populations, along with increased cytokine production [ 13 , 22 ]. Therefore, these studies reported that probiotics affect both innate and acquired immunity in humans and chicks [ 13 , 14 , 22 , 23 , 24 ]. This study evaluated the effects of probiotics on growth and immune status of liver and secondary lymphoid organ in piglets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations